INVESTIGATION OF CHILDREN FANTASY LITERATURE IN ENGLISH LANGUAGE: THE CASE OF BEATRIX POTTER’S WORK/INVESTIGASI SASTRA FANTASI ANAK-ANAK DALAM BAHASA INGGRIS: CASE OF BEATRIX POTTER’S WORK - Ali Ashrafi (Aksara, 2020)
Abstract In this research, we chose the series of Beatrix Potter in English languages. Then the obtained data studied in three parts of the style of writing, the semiotics of fantasy characters, and in terms of social concepts such as power, gender, and collaboration. This research is descriptive research based on the library method. Fantasy is a ction about a topic in the past or an event in the future that is now untrue, but relying on individual knowledge and imagination. Fantasy literature, as it stands today, was created in Europe in the eighteenth century, although its elements exist in myths and ancient myths. Beatrix Potter (1866-1943) grew up in London is the most acclaimed Baby Writer. She was an English writer, illustrator, natural scientist, and conservationist best known for her children’s books featuring animals. She is well-known as the author of children’s books such as The Tale of Peter Rabbit. She wrote 23 books altogether, the most famous of which was “the Tale of Peter Rabbit “, which translated into 35 languages and printed 151 million copies in the world. Keywords: characterization, fantasy literature, story, Beatrix Potter, phantom fantasy, realistic fantasy, writing style Abstrak Dalam penelitian ini, dipilih seri Beatrix Potter dalam bahasa Inggris. Kemudian data yang diperoleh dianalisis dalam tiga bagian: gaya penulisan, semiotika karakter fantasi, dan ditinjau dari konsep sosial, seperti kekuasaan, jenis kelamin, dan kolaborasi. Penelitian ini merupakan penelitian deskriptif berdasarkan metode kepustakaan. Fantasi adalah ksi tentang suatu topik di masa lalu atau peristiwa di masa depan yang sekarang tidak benar, tetapi mengandalkan pengetahuan dan imajinasi individu. Sastra fantasi, seperti yang ada saat ini, diciptakan di Eropa pada abad kedelapan belas, meskipun unsur-unsurnya ada dalam mitos dan mitos kuno. Beatrix Potter (1866-1943) besar di London adalah Penulis Bayi, ilustrator, ilmuwan alam, dan konservasionis yang terkenal karena buku anak-anaknya yang menampilkan hewan. Karyanya yang terkenal adalah buku anak-anak, seperti The Tale of Peter Rabbit. Kata kunci: penokohan, sastra fantasi, cerita, Beatrix Potter, fantasi hantu, fantasi realistik, gaya menulis